Targeting JNK3: An In-silico Approach to Uncover Potential Therapeutics for Alzheimer’s Disease - Kashif, Mohd; Nagarajan, Balaji; Desai, Umesh R.; Pandurangan, Ashok Kumar (CNS & Neurological Disorders - Drug Targets, 2025)
<span class=
Keywords: JNK3